In vivo preclinical assessment of novel 68Ga-labelled peptides for imaging of tumor associated angiogenesis using positron emission tomography imaging. (August 2021) - Dénes, Noémi; Kis, Adrienn; Szabó, Judit P.; Jószai, István; Hajdu, István; Arató, Viktória; Enyedi, Kata Nóra; Mező, Gábor; Hunyadi, János; Trencsényi, György; Kertész, István
Abstract: Formation and growth of metastases require a new vascular network. Angiogenesis plays an essential role in the expansion and progression of most malignancies. A high number of molecular pathways regulate angiogenesis, including vascular endothelial growth factor (VEGF), αv β3 integrin, matrix metalloproteinases (MMPs), or aminopeptidase N. The aim of this study is to involve new, easily accessible peptide sequences into the of neo-angiogenesis in malignant processes. Labelling of these peptide ligands with 68 Ga enable PET imaging of neo-vascularization. Highlights: Receptor selective peptides can play an important role in PET imaging VEGFR-1, αv β3 integrin, or APN can be a target to visualize neo-angiogenesis Properties of the biological vector determines the behaviour of the probe The 68 Ga-labelled peptides showed accumulation on the examined B16F10 cell line